The Influence Work Environment and Labor Discipline Regarding the Performance of Employees in the Production Division of PT Berkat Ganda Sentosa - Dary; Sulastri Irbayuni (Indonesian Journal of Business Analytics, 2023)
The purpose of this study is to investigate how the workplace environment affects assess employee performance and the impact of employee work discipline. This research collects data by distributing questionnaires to the employees of the production department at PT. Berkat Ganda Sentosa. Variables used in this study include: The independent variables are work environment (X1) and work discipline (X2), and the dependent variable is performance (Y). Partial Least Squares Analysis Model (PLS) is used in this study. It is a method of creating a model that is conceivable when several factors are considered. The results of this study indicate that work environment does not contribute to employee performance, and that appropriate work discipline may improve PT Berkat Ganda Sentosa performance.